2023
DOI: 10.1021/acsptsci.2c00229
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Landscape of Cell-Penetrating Peptide-Mediated Organelle Restoration and Replacement

Abstract: Organelles are specialized subunits within a cell membrane that perform specific roles or functions, and their dysfunction can lead to a variety of pathophysiologies including developmental defects, aging, and diseases (cancer, cardiovascular and neurodegenerative diseases). Recent studies have shown that cell-penetrating peptide (CPP)-based pharmacological therapies delivered to organelles or even directly resulting in organelle replacement can restore cell function and improve or prevent disease. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 153 publications
0
8
0
Order By: Relevance
“…Sclerostin inhibitors, 177,178 such as Romosozumab, 179,180 Blosozumab, and BSP804, 181 target sclerostin to boost bone density in OI patients. 61,182,183 Studies have shown increased bone formation and bone mass in OI patients receiving these inhibitors, but there is a rapid loss of bone mass when the medication is stopped, which can be mitigated with bisphosphonates.…”
Section: Acs Pharmacology and Translational Sciencementioning
confidence: 99%
“…Sclerostin inhibitors, 177,178 such as Romosozumab, 179,180 Blosozumab, and BSP804, 181 target sclerostin to boost bone density in OI patients. 61,182,183 Studies have shown increased bone formation and bone mass in OI patients receiving these inhibitors, but there is a rapid loss of bone mass when the medication is stopped, which can be mitigated with bisphosphonates.…”
Section: Acs Pharmacology and Translational Sciencementioning
confidence: 99%
“…Several intracellular targets involved in different stages of the viral life cycle have been identified as potential targets for nanobodies to inhibit SARS-CoV-2 replication and packaging, such as Mpro, RdRp, and viral N protein. , Although nanobodies’ small size enables us to effectively target intracellular proteins and other targets involved in various cellular pathways, delivering nanobodies into the cytoplasm of target cells is a significant challenge due to the presence of cellular membranes that prevent their entry. There are several approaches to deliver nanobodies into the cytoplasm, including chemical conjugation, cell-penetrating peptides, and nanoparticle-based delivery systems. , These methods have been used successfully for the delivery of other therapeutic molecules. Thus, the development of nanobodies targeting intracellular targets involved in SARS-CoV-2 replication still holds promise for the development of new therapeutics to combat COVID-19.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…It was first reported in Wuhan, China, in December 2019 and has since become a global pandemic. 1 There have been 768,983,095 confirmed cases of COVID-19 and 6,953,743 deaths worldwide as of August 2023 according to the World Health Organization (WHO). 2 The virus belongs to the family of coronaviruses and shares 79% genome sequence identity with severe acute respiratory syndrome coronavirus (SARS-CoV) and 50% with Middle East respiratory syndrome virus (MERS-CoV), which are two other viruses in the same virus family.…”
mentioning
confidence: 99%